On some inaccuracies in translation of “The Secret History of the Mongols” by A.S. Kozin - Fidarov R.F. (Золотоордынское обозрение)
Research objectives: This paper aims to identify inaccuracies in the Russian translation by A.S. Kozin of paragraphs 270 and 275 of the Mongolian 13th-century historical text “The Secret History of the Mongols.” These inaccuracies hinder a proper understanding of the information presented. The paragraphs in the source text narrate events related to the organization and course of the Great Western campaign of the Mongols (1236–1242). The translations sometimes present information that contradicts other sources and, consequently, modern interpretations of the history of the 1236–1242 Campaign. Furthermore, the points noted are occasionally refuted by other information within the same source. The analysis of these excerpts, which are ambiguous in meaning, leads to the conclusion that mistakes were made in their Russian translation. Notably, the inaccuracies identified in A.S. Kozin’s translation have not been previously addressed by researchers. Errors in the translation of the source material hinder the accurate comprehension and interpretation of its content by Russian-speaking researchers, occasionally leading modern authors astray and potentially resulting in incorrect conclusions. Research materials: This study focuses on specific information in the Russian translation by A.S. Kozin of paragraphs 270 and 275 of the Mongolian historical text “The Secret History of the Mongols.” The investigation was conducted by comparing questionable segments with translations of the source text in other European languages, as well as with re-transcriptions of the text into Mongolian carried out by specialists. Results and novelty of the research: This paper exposes inaccuracies in A.S. Kozin’s Russian translation of “The Secret History of the Mongols” and proposes their correction. A thorough understanding of the source material is crucial for its accurate interpretation and drawing of correct conclusions. This study may be of particular interest to Russian-speaking researchers.